Evaluation of CKD-EPI and MDRD Prediction Equations for Estimation of GFR in Lean and Obese Bangladeshi Subjects (Journal of Scientific Research, 2012)
Glomerular filtration rate (GFR) is the filtrate produced by the kidneys in each minute. Chronic kidney disease epidemiology (CKD-EPI) and standardized modification of diet in renal disease (MDRD) equations are the commonly used equations to estimate GFR. Evaluation of GFR prediction equations regarding body mass index is not available in Bangladeshi population. In this study we compared estimated GFR (eGFR) with GFR measured by creatinine clearance rate (CCR) in lean and obese Bangladeshi subjects. Measured GFR were 40±21 and 45±22 ml/min/1.73m2 in lean and obese groups, respectively. Compared to measured GFR, estimated GFRs were 7.5 (p